If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6-2x-2=0
We simplify the equation to the form, which is simple to understand
3x+6-2x-2=0
We move all terms containing x to the left and all other terms to the right.
+3x-2x=0-6+2
We simplify left and right side of the equation.
+1x=-4
We divide both sides of the equation by 1 to get x.
x=-4
| 3(t-3)-2+=-30 | | 0.2x^2-1.2x+0.2=0 | | x-10=6x+9 | | 2x+2x=12 | | 3(t-3)-2=-30 | | -7X+5[X-7]=-27 | | 3(x+2)+50=-4x | | 9+3(5y+3)= | | 4x+7=49 | | -40-8x=10x+22 | | 4x+8=-8-9x | | -6=3(y+2) | | 1/3(x+4)+1/5(x+3)=3 | | 4562= | | 3x+2x=25-15 | | -7x-2x=36 | | 1/5(2x+8)=x+1 | | 6-2x=2(15-x) | | a+5(3-a)=11 | | -9V-5+6V=19 | | (x+10)/3=(x+5)/2 | | 3y+50-5y=70 | | m^2+22m+23=0 | | 1/4(x+6)=1/3(x+4) | | 2x^2+14x+2165=0 | | 265-2x=43x+20 | | 22m+23+m^2=0 | | x/3-3=2 | | D+1=7 | | F=-30 | | 8-10x=60-24x | | 2x+2+9x=13 |